Incidencia de la investigación y desarrollo en el crecimiento económico: evidedencia empírica para américa latina, periodo 1996-2018. - Montenegro Ordoñez, Karla Janeth (2022)
One of the factors influencing economic growth is technology, which has been generated by the constant industrial evolution that has occurred over time. With the objective of determining the incidence of research and development in economic growth with evidence for Latin America during the period 1996-2018. The statistical sources of the World Bank (2020) and Penn World Table (2019) used a GLS model and second-generation econometric techniques in the presence of cross-dependence, using the Westerlund test (2007), Fully Modofied Ordinary Least Squares (FMOLS) and Granger’s causality through Dumitrecu and Hurlin (2012). Thus, the results mention a positive relationship in Latin America and in all countries classified by their income level, fulfilling the hypothesis raised. It should be noted that there is short- and long-term cointegration between economic growth and research and development. The policy implications are aimed at encouraging public investment in this area and improving production processes.